ASSESSMENT OF SELECTED PHYSICO-CHEMICAL PARAMETERS OF GROUND WATER IN DIRECT CONTACT WITH SEPTIC TANKS: EXPERIMENTAL MODELING - KOCHARY, SHAWKAT AHMED YASEEN; NOORI, BAHZAD MOHAMMAD ALI; BYL, TOM D. (Journal of Duhok University, 2017)
The purpose of this study was to assess the effect of non-regulated (and directly contacted) septic tanks on ground water quality through designing a laboratory physical vadose model (PVM) with a vertical flow direction. The model was packed with silt-Clay soil using a new packing approach other than the ordinary (standard, modified and static) compaction methods, which was adopted upon its homogeneity and efficiency approval. The effect of septic tanks as an exclusive source of contaminants was represented by supplying the designed model with newly collected septic water (black water from a septic tank). Preliminary in-situ soil tests were conducted to better represent the lithology of area of this study. The model was run for a period of three months and water samples were collected on daily basis however, weekly analyzed. Selected physical and chemical parameters were studied for assessment including pH, Temperature, Dissolved Oxygen (DO), Electrical Conductivity (EC), Total Hardness (TH), Ammonium (NH4-N), Nitrate (NO3¯N), and Phosphorus (P). Analytical results were used to identify and model trends to estimate and predict future trends, which mostly led to a conclusion of bad category and very low ground water quality as a result of its direct contact with non-regulated septic tanks. This study helped the local government in establishing precaution strategies for ground water management in order to protect the public health.